2014
DOI: 10.1146/annurev-psych-010213-115134
|View full text |Cite
|
Sign up to set email alerts
|

A Century of Selection

Abstract: Over 100 years of psychological research on employee selection has yielded many advances, but the field continues to tackle controversies and challenging problems, revisit once-settled topics, and expand its borders. This review discusses recent advances in designing, implementing, and evaluating selection systems. Key trends such as expanding the criterion space, improving situational judgment tests, and tackling socially desirable responding are discussed. Particular attention is paid to the ways in which te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(126 citation statements)
references
References 173 publications
2
123
0
1
Order By: Relevance
“…In addition to their own personal beliefs about employee selection (Furnham, 2008;Nolan & Highhouse, 2014), practitioners consider the beliefs of others who are stakeholders in the hiring process when determining the approaches used to make employment decisions (Ryan & Ployhart, 2014). These stakeholders include current and future job candidates (König, Klehe, Berchtold, & Kleinmann, 2010) as well as organizational colleagues and management (Terpstra & Rozell, 1997;van der Zee et al, 2002).…”
Section: Decision Making For Employee Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their own personal beliefs about employee selection (Furnham, 2008;Nolan & Highhouse, 2014), practitioners consider the beliefs of others who are stakeholders in the hiring process when determining the approaches used to make employment decisions (Ryan & Ployhart, 2014). These stakeholders include current and future job candidates (König, Klehe, Berchtold, & Kleinmann, 2010) as well as organizational colleagues and management (Terpstra & Rozell, 1997;van der Zee et al, 2002).…”
Section: Decision Making For Employee Selectionmentioning
confidence: 99%
“…Studies employing the theory of planned behavior (Ajzen, 1991), for example, have repeatedly demonstrated that behavioral intentions are influenced by normative beliefs concerning the likelihood that important individuals or groups approve of the behaviors (i.e., subjective norms). In the context of employee selection, research likewise suggests that practitioners' use of employee selection practices is meaningfully influenced by their beliefs about the ways in which the practices are viewed by others who are stakeholders in the hiring process (König, Klehe, Berchtold, & Kleinmann 2010;Ryan & Ployhart, 2014;Terpstra & Rozell, 1997). Van der Zee et al (2002), for example, found that practitioners' intentions to use structured and unstructured interviews were significantly influenced by theirs concerns about coworkers' approval of the practices.…”
Section: Studymentioning
confidence: 99%
“…Although in some cases the widespread use of telephone assessment may be impractical, the telephone also has benefits such as being able to reach people almost anywhere, being a familiar communication tool, and being inexpensive (Baca et al, 2007). Most recently, the need for ongoing evaluation of the role of technology in selection and assessment (Ryan & Ployhart, 2014) has been noted. If, as results from the current study indicate, online and telephone tests can be faked no more than pen-and-paper tests within a vocational context, then these delivery modes may be used with increased confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Often, a psychologically-based assessment is used in an attempt to recognize factors that cannot easily be seen in applicants during the screening and selection process. As Ryan and Ployhart (2014) state, "Over 100 years of psychological research on employee selection has yielded many advances, but the field continues to tackle controversies and challenging problems, revisit once-settled topics, and expand its borders." In fact, Diekmann and Konig (2015) review why people either love personality assessment, choose to leave it alone, or simply do not understand the results.…”
Section: Introductionmentioning
confidence: 99%